The Effect of Insulation Defects on Electric and Magnetic Field Distributions in Power Cables - Uydur, Cihat Cagdas; Arikan, Oktay; Kalenderli, Ozcan (UNIV OSIJEK, TECH FAC, 2021)
In this article, electrical and magnetic field analysis in XLPE insulated power cables is performed. The defects that may occur in the insulation material have been tried to be realized considering different conditions. A lot of variations have been obtained by changing the location of the defect in the insulation material, the shape of the defect, the size of the defect and the type of the defect. The effect of all the factors that make up the defect on the distribution of the electric field and magnetic field is shown and the causes of malfunction in the cable are examined. The electric field analysis for 1 x 240/25 mm(2) was performed by using different forms with equal areas. The magnetic field analysis was performed for balanced and unbalanced load cases to 3 x (1 x 240/25) mm(2) and 3 x 240/25 mm(2) cable with XLPE insulation.
Keywords: aging; electric field; insulation defect; magnetic field; XLPE cable; Engineering